Visit to general practitioners as a proxy for accessing chronic benefits by members of medical schemes, South Africa - Mncedisi M. Willie; Monwabisi Gantsho (AOSIS, 2012)
Background: Prescribed Minimum Benefits is a list of conditions that all medical schemes need to cover in full, and includes a select of chronic conditions. Chronic conditions affect people's lifestyles and require ongoing management over a period of years for long-term survival.Objectives: This study examined the association between prevalence of selected chronic diseases and health service use, in particular visits to general practitioners (GPs) by medical scheme members.Method: This was a retrospective study on medical schemes data. The median imputation method was employed to deal with missing and unreported chronic diseases prevalence. Multivariate logistic regression analysis was employed to assess effects of chronic diseaseprevalence, age stratum and scheme size on GP visits per annum.Results: The study showed that prevalence of asthma was significantly associated with more than three GP visits (OR = 1.081; 95% CI = 1.008-1.159), as was prevalence of type 2 diabetes (OR = 1.087; 95% CI = 1.027-1.152), whilst prevalence of hyperlipidaemia (OR = 0.92; 95%CI = 0.875-0.97) was more likely to be associated with less than three GP visits. Prevalence of hypertension was associated with more than three GP visits per year (OR = 1.132; 95% CI = 1.017-1.26).Conclusion: This study shows that scheme size, prevalence of chronic diseases such as asthma, type 2 diabetes, hyperlipidaemia and hypertension are related to GP visits. GPs and managed care programmes employed by schemes should give special attention to certain disease states with high prevalence rates in an effort to better manage them.